Educators’ conception of student assessment and their practices in an institution of education in MARA - Mohamad Mustafa, Maslina; Abdul Manaf, Umi Kalthom (Human Resource Management Academic Research Society, 2019)
Despite existing research on the educators’ conception of student assessment, few studies have attempted to explore this topic among tertiary education system in Malaysia. In response to this gap, this is a concept paper aimed to explore educators’ conception of student assessment and their practices among MARA Professional College lecturers’ (N = 50). Descriptive quantitative method will be used to investigate the lecturers’ conception of student assessment regarding improvement, school accountability, student accountability and irrelevance as well as the relations between different conceptions purposes and their assessment practices. Acquiring further knowledge on assessment will have profound effect on the teachers’ assessment practice. Related organizations should work together in improving the training related to assessment.